Optimizing Health Service Delivery: Addressing Non -Value Added Activities through Lean Six Sigma - Anggi Pranata (Institute of Accounting Research and Novation (IARN), 2024)
This research explores the application of Lean Six Sigma principles in optimizing health service delivery, with a focus on identifying and addressing non - value added activities within healthcare processes. Through a systematic analysis, including process mapping, root cause analysis, and impact assessment, this study identifies key inefficiencies and their implications for healthcare providers, patients, and other stakeholders. The findings underscore the critical importance of waste reduction, process standardization, continuous improvement, and patient-centered care in driving transformative change and achieving sustainable improvements in efficiency, quality, and patient satisfaction. The implications of the findings extend beyond healthcare providers to policymakers, payers, and community organizations, highlighting the potential for system-wide improvements and cost savings. By embracing Lean Six Sigma principles and fostering a culture of continuous improvement, healthcare organizations can enhance value delivery, drive innovation, and ultimately improve the health and well-being of individuals and communities. This research contributes to the broader body of knowledge on Lean Six Sigma applications in healthcare quality improvement and provides practical insights for healthcare leaders and practitioners seeking to optimize health service delivery.